Development of Audiovisual-Based Parenting E-Modules to Stimulate Children's Cognitive Development in Kindergarten - Oly Cintia Rita; Dadan Suryana; Rakimahwati; Nurhafizah (Jurnal Penelitian Pendidikan IPA, 2026)
This study addresses the suboptimal cognitive development of early childhood, particularly in reasoning and problem-solving skills, which is influenced by limited parental knowledge and gaps in digital literacy. The objective of this research is to develop an audiovisual-based parenting E-module that is valid, practical, and effective as a home-based learning guide to stimulate children's cognitive development. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The product was validated by material and media experts, while practicality and effectiveness were examined through limited trials involving parents of children aged 5–6 years in kindergarten. Data were collected using validation sheets and parent response questionnaires, and analyzed using descriptive quantitative techniques. The results indicate that the developed E-module achieved a very high level of validity, with material validation reaching 90% and media validation 86.75%. The practicality test showed a score of 92.7%, categorized as very practical, indicating that the module is easy to use, accessible, and understandable for parents. From the effectiveness perspective, findings reveal an increase in parents’ understanding, confidence, and ability to implement cognitive stimulation activities at home. These results suggest that the integration of audiovisual elements facilitates meaningful learning experiences and reduces cognitive load for users. In conclusion, the audiovisual-based parenting E-module is a feasible and effective educational tool to support early childhood cognitive development. It has strong potential to enhance parental involvement and can be utilized as an alternative digital parenting resource, particularly in contexts with limited access to structured learning materials.